Precise Measurement of Cat Patellofemoral Joint Surface Geometry with Multistation Digital Photogrammetry. - Ronsky, J.; Boyd, S.; Lichti, Derek; Chapman, M.; Salkauskas, K. (American Society for Mechanical Engineers, 1999)
Three-dimensional joint models are important tools for investigating mechanisms related to normal and pathological joints. Often these models necessitate accurate three-dimensional joint surface geometric data so that reliable model results can be obtained: however, in models based on small joints, this is often problematic due to limitarions of the present techniques. These limitations include insufficient measurement precision, the requirement of contact for the measurement process, and lack of entire joint description. This study presents a new non-contact method for precise determination of entire joint surfaces using multistation digital photogrammetry (MDPC) and is demonstrated by determining the cartilage and subchondral bone surfaces of the cat patellofemoral (PF) joint. The digital camera-lens setup was precisely calibrated using 16 photographs rranged 10 achieve highly convergent geometry to estimate interior and distortion parameters of the camera-lens setup. Subsequently, six photographs of each joint surface were then acquired for surface measurement. The digital images were directly imported to a computer and newly introduced semi-automatic computer algorithms were used to precisely determine the image coordinates. Finally, a rigorous mathematical procedure named the bundle adjustment was used 10 determine the three-dimensional coordinates of the joint surfaces and to estimate the precision of the coordinates. These estimations were validated by comparing the MDPG measurements of a cylinder and plane to an analytical model. The joint surfaces were successfully measured using the MDPG method with mean precision estimates in the least favorable coordinate direction being 10.3 pm for subchondral bone and 17.9 pm for cartilage. The difference in measurement precision for bone and cartilage primarily reflects differences in the translucent properties of the surfaces.